(untitled) (Eurasian Medical Research Periodical, 2023)
Parkinson’s disease is considered one of the current topics of today’s neurology and geriatrics. Today, the etiology, pathogenesis of this disease and the risk of complications caused by the disease are being thoroughly studied[4,6]. One of the risks of such complications is cognitive impairment. Today’s neurology shows that cognitive disorders are caused by dopamine metabolism disorders, cerebral blood circulation disorders, changes in substance metabolism and a number of other factors[8.12,13]. One of the proposed causes and theories is the change in the plasma concentration of the hormone cortisol in Parkinson’s disease. Although the role of hormone changes in Parkinson’s disease in causing cognitive disorders has not been fully confirmed, this theory has been supported by several years of research by a number of scientists